The Persian version of the body esteem scale among Iranian adolescents: a translation, psychometrics, and network analysis - Sharif-Nia, Hamid; Sivarajan Froelicher, Erika; She, Long; Jafari-Koulaee, Azar; Hejazi, Sima; Mosazadeh, Hasan; Goudarzian, Amir Hossein; Hasan Nejad, Ghaem (Frontiers in Psychology, 2024)
Introduction: The psychometric properties of the Body Esteem Scale have not been assessed in Iran. Therefore, the aim of this study was to translate and determine the validity and reliability of the Persian version of the Body Esteem Scale in the Iranian adolescents. Methods: The sample of this methodological study consisted of 504 adolescents [mean age: 16.55 (SD= 1.54) years] living in Tehran City, Iran. After translation of the scale, content validity (quantitative and qualitative), structural (exploratory and confirmatory factor analysis), convergent and discriminant validity of it were evaluated. Exploratory graph analysis was done to determine the number of factors. Cronbach's alpha, Composite Reliability, and Maximal Reliability were calculated. Results: In content validity evaluation step, all items had acceptable scores and were retained. The results of exploratory factor analysis with Promax rotation and exploratory graph analysis extracted three factors accounting for 49.49% of the variance comprising 18 items. Also, after necessary modifications during CFA, the final model was approved. Convergent and discriminant validity were confirmed. The Cronbach’s alpha, CR, and MaxR for all constructs were greater than 0.7, demonstrating good internal consistency and construct reliability. Conclusion: According to results, Persian version of body esteem scale has valid structure and acceptable reliability. Health professionals in many ways can use this scale.